Development of a design and implementation process for the integration of hydrokinetic devices into existing infrastructure in South Africa - Niebuhr, CM; Van Dijk, M; Bhagwan, JN (Water SA, 2019)
In South Africa there is currently no notable use of modern small-scale hydrokinetic (HK) energy systems, mainly due to formerly low-cost coal-powered electricity. This renewable energy option makes use of the kinetic energy from flowing water, rather than potential energy, which is more often used in conventional hydropower. Updated refined versions of this technology are now being investigated and manufactured due to the global drive towards reducing carbon emissions and increasing energy efficiency. These modular units allow for installation of HK turbines into existing water infrastructure with very little civil works. The study’s objective was to develop a simplified design and implementation process for HK devices within the South African legislative and regulatory environment. Approximately 66% of South Africa’s water supply is used by the agricultural sector with more than 6 500 km of canal systems running through many areas which could benefit from alternative energy sources. The recent electricity crisis in the country allowed for problem resolution through funding opportunities and thereby an introduction of an innovative and sustainable technology to provide renewable electricity where otherwise not feasible. A pilot HK project was implemented in an applicable section on the Boegoeberg irrigation canal in the Northern Cape Province and tested for optimum functionality and correct application. This process allowed evolution of a development process for the implementation of HK devices in existing water infrastructure.